An interventional study regarding knowledge and awareness of TB and HIV among high school children in rural and urban areas of Dehradun - Natt, Harsimranjit K.; Sharma, Ashwani; Luthra, Megha; Ohri, Puneet; Negi, Kamal S. (International Journal Of Community Medicine And Public Health, 2019)
Background: The World Health Organization Global TB report reported that TB ranks alongside HIV as a leading cause of death worldwide. Evidence based studies revealed that knowledge and awareness has a substantial impact on the prevention of HIV/AIDS and tuberculosis. This study was conducted to compare the awareness and knowledge of high school children regarding HIV and TB in the rural and urban areas and to assess the impact of educational intervention on the same. Methods: One school each from rural and urban field practice area was selected by purposive sampling technique. A total of 205 high school students were included in the study by total enumeration method. An interventional study was conducted regarding awareness and knowledge about TB and HIV/AIDS by means of health talk and help of audio visual aids. The data was collected in a predesigned self administered questionnaire by pretest and post test method. Results: The total of 205 students participated in the study. Majority of the respondent have correct knowledge regarding the causative agent of TB (38.5%) with 28.4% in rural and 48.5% in urban area. Moreover majority of the respondent correctly elicited the causative agent of HIV/AIDS (52.6%) with 44.1% in rural and 61.1% in urban area. Overall the intervention had a substantial effect on the awareness and knowledge level of the students regarding HIV/AIDS and tuberculosis. Conclusions: Although awareness among the masses is there but right knowledge and practice plays a pivotal role in improving the health status and awareness of the community.